2020
DOI: 10.1016/j.radcr.2019.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular joint herniation into the middle ear: A rare cause of mastication-induced tinnitus

Abstract: A 75-year-old patient complained of mastication-induced clicking tinnitus on the left side, and otoendoscopic examination revealed that the left tympanic membraneTM was outwardly bulged by clenching her teeth. Temporal bone computed tomography demonstrated that the posteromedial bony wall of the glenoid was partially dehiscent, allowing herniation of soft tissue contents of temporomandibular joint into the middle ear. Increased middle ear pressure due to soft tissue herniation can induce left tympanic membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Subjective tinnitus refers to a phantom perception, whereas objective tinnitus refers to perceived sounds generated from an acoustic source located within the body. Pathologies causing objective tinnitus are rather heterogeneous and research to understand and treat this form of tinnitus is ongoing (Liu et al, 2019;Choi et al, 2020). It is, however, far less common than subjective tinnitus and its underlying mechanisms are usually clearer (Tunkel et al, 2014).…”
Section: Overviewmentioning
confidence: 99%
“…Subjective tinnitus refers to a phantom perception, whereas objective tinnitus refers to perceived sounds generated from an acoustic source located within the body. Pathologies causing objective tinnitus are rather heterogeneous and research to understand and treat this form of tinnitus is ongoing (Liu et al, 2019;Choi et al, 2020). It is, however, far less common than subjective tinnitus and its underlying mechanisms are usually clearer (Tunkel et al, 2014).…”
Section: Overviewmentioning
confidence: 99%
“…Although there is a paucity of data in the natural history of asymptomatic persistent FH, the authors do not feel that observation in asymptomatic patients would increase the risk of complications in the future. 5,6,[8][9][10]13,15,17 Further work is warranted to better understand both the natural history of this pathology as well as the prevalence of symptomatic disease among patients with radiographically confirmed dehiscences.…”
Section: Resultsmentioning
confidence: 99%
“…Although incidental persistent FH is diagnosed in 11.5%-20% of individuals undergoing temporal bone imaging, few studies have described the clinical nature of this pathology. [2][3][4] Available literature reports on single cases [5][6][7][8][9][10][11][12][13][14] or small case series 15,16 that highlight the presentation and management variability associated with this pathology. Understanding of this pathology from the lone review examining temporomandibular joint herniation into the EAC is limited given the wide variance in literature and the presentation of all EAC fistula patients, including spontaneous and non-spontaneous fistulae, as a single group in this study; therefore, conclusions are restricted when looking specifically at persistent FH.…”
mentioning
confidence: 99%
“…Choi et al and Lim et al reported cases of clicking tinnitus with clenching teeth, while there was no history of trauma or surgery in the TMJ region. The CT scan of the temporal bone indicated a bony defect in the posteromedial wall of glenoid fossa, and the otoscopic examination indicated TMJ herniation through FH into EAC [ 28 , 36 ].…”
Section: Discussionmentioning
confidence: 99%